2009
DOI: 10.1088/0960-1317/19/10/105027
|View full text |Cite
|
Sign up to set email alerts
|

A catheter-type flow sensor for measurement of aspirated- and inspired-air characteristics in the bronchial region

Abstract: We developed a novel catheter-type flow sensor for measuring the aspirated- and inspired-air characteristics trans-bronchially. An on-wall in-tube thermal flow sensor is mounted inside the tube, and it is used as a measurement tool in a bronchoscope. The external diameter of the tube is less than a few mm, and therefore, it can evaluate the flow characteristics in the small bronchial region. We newly developed a fabrication process to miniaturize it to less than 2.0 mm in the external diameter by using a heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…We previously developed a catheter flow sensor that could be used to trans-bronchially measure aspirated-and inspired-air flow characteristics for precise evaluation of chronic obstructive pulmonary disease and confirmed that it could measure the breathing characteristics at the air passage of mice under anesthesia conditions (Shikida et al 2009(Shikida et al , 2010Yamada et al 2014a). The whole surface of the outside tube in the developed catheter flow sensor was tightly fixed onto the inside surface of the air passage in the measurements in these experiments.…”
Section: Introductionmentioning
confidence: 92%
“…We previously developed a catheter flow sensor that could be used to trans-bronchially measure aspirated-and inspired-air flow characteristics for precise evaluation of chronic obstructive pulmonary disease and confirmed that it could measure the breathing characteristics at the air passage of mice under anesthesia conditions (Shikida et al 2009(Shikida et al , 2010Yamada et al 2014a). The whole surface of the outside tube in the developed catheter flow sensor was tightly fixed onto the inside surface of the air passage in the measurements in these experiments.…”
Section: Introductionmentioning
confidence: 92%
“…The sensor allowed diagnosing sleep-specific respiration disturbances that are a risk factor for basic cardiovascular diseases [47]. The sensing element (Figure 2(a)) provided a short response time (about 2 ms), wide flow range (up to about 400 L·min and showed a response time of about 100 ms [50]. The same author designed an anemometer for evaluating nasal respiration with a measurement range up to 2 L·min ) to implement the principle of hot-wire anemometry (Figure 2(b)): one diode, heated by a polysilicon resistor, was placed on a silicon membrane [52]; another unheated diode measured the environmental temperature.…”
Section: Thermal Flow Sensors: Biomedical Applicationsmentioning
confidence: 99%
“…However, breathing characteristics are difficult to evaluate directly at lesions region. Thus, microelectromechanical systems (MEMS) technologies were previously applied to produce a novel miniaturized flow sensor to precisely evaluate COPD ( Figure 1) [2]. This flow sensor can measure breathing characteristics in lesions with high accuracy because it is inserted in lesioned parts directly.…”
Section: Introductionmentioning
confidence: 99%